Assessment of the knowledge of female students of the Medical University of Warsaw regarding the prevention of HPV infections - Kalita-Kurzyńska, Kinga; Duda-Zalewska, Aneta (Nursing in the 21st Century, 2022)
ASSESSMENT OF THE KNOWLEDGE OF FEMALE STUDENTS OF THE MEDICAL UNIVERSITY OF WARSAW REGARDING THE PREVENTION OF HPV INFECTIONSIntroduction. According to the WHO, the health consequences of HPV infections constitute a serious public health problem. In order to avoid HPV infections, the primary prevention, mainly vaccination, plays a crucial role.Aim. The aim of the study is an assessment of the knowledge about HPV infection prevention of female students from diff erent degree courses at the Medical University of Warsaw.Material and methods. The study was conducted among 181 female students who studied one of three degree courses: nursing, midwifery and public health, using a diagnostic survey. The tool of the study was the author’s questionnaire. The independence test χ² was used for statistical analysis. The statistical signifi cance was assumed to be: p